Zmarli mówią - dialogi elizejskie, najwybitniejsi twórcy i ich utwory - Urbańska, Monika (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2005)
The study deals with the history of development of the genre dialogues of the dead. Most authors of the dialogues drew inspiration from creation of a poet Lukian from Samosat. The genre especially flourished in XVIIIth century France. The greatest French authors of dialogues were: Boileau, Fontenelle and Fénelon. Boileau was the author of the first significiant dialogues U's Heros de roman, dialogue á la maniere de iMcien which was published in 1773. Fontenclle made his début in field of dialogues of the dead in 1683 writing anonymous Nouveaux dialogues des morls. His dialogues are full of scepticism and believing in fatum. The third of the greatest - Fénelon was a teacher and educator of a young prince Lewis. That is why his dialogues has didactic character and clear pointed end. Not uncommonly Fénelon starts dialogues with a preface with moral admonition to young readers. In many dialogues Fénelon condemns bad, cruel rulers oposing to them righteous and good kings. The study deals with an original Polish dialogues of the dead as well. The first Polish dialogues came from first half of XVI“1 century. Theirs authors were F. Bohomolec and I. Krasicki. The former published in 1758 the dialogue A conversation upon Polish language, the latter wrote 30 dialogues which express author’s reflections about difficult political situation of fatherland, about windings o f human nature. His dialogues are didactic in character, similiary to Fénelone’s. The difference is that Krasicki had been writing for adult readers. Many Polish dialogues are to this day anonymous. Many dialogues of metioned in the study authors were published in Polish periodicals: Zabawy Przyjemne i Pożyteczne (1770 1777), Monitor (1765- 1785), Zbiór Różnego Rodzaju Wiadomości z Nauk Wyzwolonych (1770).